Оцінка фізичних факторів середовища в салонах краси - Сидоров, Олександр Володимирович; Богомазюк, Яна Юріївна; Майданець, Анжела Вікторівна (НТУ "ХПІ", 2015)
Робота присвячена дослідженню фізичних факторів середовища (температура та вологість повітря, швидкість переміщення повітря, шум, освітленість приміщень, електростатичне поле, електромагнітне випромінювання, іонізуюче випромінювання, легкі аероіони) у салоні краси «НІККО» (м. Буча, Україна). Метою роботи було оцінити відповідність рівнів фізичних факторів середовища у салоні краси встановленим нормативним вимогам та розробити заходи з нормалізації цих факторів у разі їх невідповідності. Новизна отриманих результатів полягає в тому, що вперше були досліджені фізичні фактори приміщень салону краси та оцінені рівні їх безпечності.

Paper has been devoted to environmental physical factors study (air temperature and humidity, air movement velocity, noise, room lightening, electrostatic field, electromagnetic radiation, ionizing radiation, light air ions) in beauty salon “NIKKO” (Bucha town). The aim of work has been to assess the compliance of environmental physical factors levels in beauty salons with established normative requirements and to develop measures on this factors normalization in the case of its incompliance. The novelty of received results includes research of beauty salon premises physical factors and their safety levels assessment conducted for the first time. The measurements have shown compliance of levels of electrostatic fields, electromagnetic radiation, ionizing radiation and average daily noise in the premises of the beauty salon with sanitary norms. The conducted assessment of measures efficiency on microclimate parameters normalization has revealed that the most effective is combination of hourly aeration of premises with air humidifier application. The increase of light air ions concentration to its minimal required level has been achieved due to this combination.
Assessment of environmental physical factors of beauty salons
Keywords: санітарні норми; нормалізація фізичних факторів; випромінювання; мікроклімат; sanitary norms; physical factors normalization